Disseminated Kaposi Sarcoma - Ma JY; Liu JW (Dove Medical Press, 2022)
Jin-Yuan Ma,1 Jia-Wei Liu2 1The Second School of Clinical Medicine, Zhujiang Hospital, Southern Medical University, Guangzhou, 510282, People's Republic of China; 2Department of Dermatology, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, National Clinical Research Center for Dermatologic and Immunologic Diseases, Beijing, 100730, People's Republic of ChinaCorrespondence: Jia-Wei Liu, Department of Dermatology, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, National Clinical Research Center for Dermatologic and Immunologic Diseases, Beijing, 100730, People's Republic of China, Tel +86-10-69151543, Fax +86-10-69151502, Email liujiawei89@sina.cnAbstract: AIDS-associated Kaposi sarcoma (KS) is the most common HIV-associated neoplasm. Disseminated Kaposi sarcoma became rare with the application of antiretroviral therapy. Oral AIDS-associated KS has prognostic relevance, indicating higher mortality than those with cutaneous lesions only. In this study, we reported a 40-year-old man presented with ulcerated violaceous plaques on his hard palate. Similar lesion can be observed on his left groin and anus, as well as on esophagus and gastric fundus under upper gastrointestinal endoscopy. Histological examination accorded with KS. After five cycles of doxorubicin, his oral, skin and esophagus lesions regressed considerably.Keywords: oral Kaposi sarcoma, AIDS-associated Kaposi sarcoma, AIDS, disseminated Kaposi sarcoma, chemotherapy